Loss of Cav1.2 channels impairs hippocampal theta burst stimulation-induced long-term potentiation. Issue 1 (1st January 2020) - Sridharan, Preethy S.; Lu, Yuan; Rice, Richard C; Pieper, Andrew A.; Rajadhyaksha, Anjali M.
ABSTRACT: CACNA1 C, which codes for the Cav 1.2 isoform of L-type Ca 2+ channels (LTCCs), is a prominent risk gene in neuropsychiatric and neurodegenerative conditions. A role forLTCCs, and Cav 1.2 in particular, in transcription-dependent late long-term potentiation (LTP) has long been known. Here, we report that elimination of Cav 1.2 channels in glutamatergic neurons also impairs theta burst stimulation (TBS)-induced LTP in the hippocampus, known to be transcription-independent and dependent on N-methyl D-aspartate receptors (NMDARs) and local protein synthesis at synapses. Our expansion of the established role of Cav 1.2channels in LTP broadens understanding of synaptic plasticity and identifies a new cellular phenotype for exploring treatment strategies for cognitive dysfunction.